The polypharmacy programme in Scotland: realistic prescribing. Issue 8 (28th August 2019) - Mair, Alpana; Wilson, Martin; Dreischulte, Tobias
Abstract : Since 2012, NHS Scotland has published a series of polypharmacy guidelines to help clinicians address the many medication‐related problems arising from multimorbidity. Here, Alpana Mair, Chair of the guideline group, Martin Wilson and Tobias Dreischulte explain how the third and latest edition of the polypharmacy guidance has been updated to place a greater emphasis on what matters to the patient.